2005
DOI: 10.1111/j.1464-410x.2005.05567.x
|View full text |Cite
|
Sign up to set email alerts
|

A description of radical nephrectomy practice and outcomes in England: 1995–2002

Abstract: OBJECTIVES To describe national trends in the practice of radical nephrectomy (RN) in England between 1995 and 2002. METHODS Data were extracted from the Hospital Episode Statistics database of the Department of Health in England between 1995/1996 and 2001/2002. Patients were included in the study if an International Classification of Diseases diagnosis code (ICD‐10) for malignant neoplasm of the kidney, renal pelvis or ureter, and an operative procedure code (OPCS‐4) describing total or partial excision of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 19 publications
2
30
0
Order By: Relevance
“…There are only 3 studies in the urological literature that have addressed waiting times for renal cancer surgery. Nuttall et al found a mean waiting time from the decision to perform radical nephrectomy to surgery of 23.6 days, 12 while Subramonian et al found a mean waiting time of 26 days from the diagnosis of RCC to surgery. 13 The third study, which was performed by Simunovic et al, showed a median of 64 days in 58 patients from the time of referral to a specialist to the day of nephrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…There are only 3 studies in the urological literature that have addressed waiting times for renal cancer surgery. Nuttall et al found a mean waiting time from the decision to perform radical nephrectomy to surgery of 23.6 days, 12 while Subramonian et al found a mean waiting time of 26 days from the diagnosis of RCC to surgery. 13 The third study, which was performed by Simunovic et al, showed a median of 64 days in 58 patients from the time of referral to a specialist to the day of nephrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…15 The major outcomes of chronic kidney disease are: loss of kidney function, sometimes leading to kidney failure; complications of reduced kidney function, such as hypertension, anaemia, malnutrition, neuropathy, and reduced quality of life; and increased risk of cardiovascular disease and mortality. [16][17][18] Because of raised awareness of important health risks associated with chronic kidney disease, 15-19 and worldwide data [8][9][10] showing the probable overuse of radical nephrectomy, we aimed to review our nephrectomy database and assess kidney function outcomes in patients undergoing surgery for small, solitary, renal cortical tumours.…”
Section: Introductionmentioning
confidence: 99%
“…6 Similarly, in England, only 4% of 2671 renal cortical tumours were treated by partial nephrectomy in 2002. 7 These data indicate that the procedure is underused despite its benefits. Recognizing this similar shortcoming at our institution, we have become actively involved in our LPN program for treatment of T1 tumours.…”
Section: Résumémentioning
confidence: 92%